Quality Translator Training: Recent Experience in Mozambique - Alfredo, Justino Manuel (The Bible translator, 2024)
During the pandemic restrictions of 2021 and 2022, the Mozambique Bible Society needed to train fifteen Bible translators from five neglected and minority languages, working spread out in four locations remote from the capital Maputo. These realities provoked debate: Was in-person training possible? Was it worth the cost? Could online remote learning do all or part of the job? Which parts, and how well? What resources could be made available? This paper sets that debate in our Mozambican context, reflects on these issues, and evaluates the actual training experience from the point of view of those responsible for teaching along with feedback from those trained, arguing that, in our situation, face-to-face, in-person learning is essential despite the high cost.